Global Rice Market Situation and Outlook - Mustafa, Shirley (2023)
Shirley Mustafa IFPRI-AMIS SEMINAR SERIES A Look at Global Rice Markets: Export Restrictions, El Niño, and Price Controls Co-organized by IFPRI and Agricultural Market Information System (AMIS) OCT 18, 2023 - 9:00 TO 10:30AM EDT